Improving the Quality of Santri Education Through Technopreneurship Combined with Digital Marketing at AIBS Sumberrejo Islamic Boarding School in Bojonegoro - Rofiqoh, Yusnia I’anatur; Nisa’, Irma Khoirun; Aini, Risa Nur; R, Zuwaroh K.; Rahmawati, Isnaini; Fitrianingrum, Cherly; M, Oeley (Indonesian Journal of Cultural and Community Development, 2023)
This study aims to analyse strategies for improving the quality of education for Islamic boarding school students through the development of technopreneurship combined with a digital marketing approach at the AIBS Sumberjo Islamic Boarding School in Bojonegoro. The background of this study is based on the urgency of transforming Islamic boarding school education in response to the challenges of the digital era and the importance of empowering students to become economically independent. The research method used is a descriptive qualitative approach with observation, in-depth interviews, and documentation techniques. The results of the study indicate that the integration of technopreneurship into the curriculum and activities of the pesantren has a positive impact on the competencies of santri, both in the fields of technology, business creativity, and the use of digital media as a means of promoting products. Digital marketing plays a significant role in expanding the market reach of products created by students and building a positive image for Islamic boarding schools. This programme also strengthens the values of independence and innovation in the Islamic-based educational process. The conclusion of this study affirms that technopreneurship integrated with digital marketing can serve as a strategic solution to enhance the quality of pesantren education in a holistic and contextual manner. Highlights: Curriculum Integration: Technopreneurship enhances student skills in technology and business creativity. Digital Expansion: Digital marketing increases product reach and promotes pesantren branding. Empowerment Values: The program fosters independence and innovation among students. Keywords: Technopreneurship, Digital Marketing, Pendidikan Santri, Pondok Pesantren, Mutu Pendidikan.